Quantitative evaluation of the effects of several weeks of static stretching on the flexibility of the rectus femoris using shear wave elastography: a before–after study - Ebihara Bungo; Miyasaka Hayato; Fukaya Takashi; Mutsuzaki Hirotaka (Journal of Ultrasonography)
The study aimed to quantitatively clarify the effects of several weeks of static stretching on the flexibility of the rectus femoris muscle using shear wave elastography.